Incidencia de microorganismos eficientes más abonos orgánicos en el comportamiento agronómico del cultivo de cilantro (Coriandrum sativum) en el cantón La Maná. - Solano Veliz, José Wilber (2013)
The present study was conducted in the La Maná Canton, province of Cotopaxi, sector La Playita, is located between the coordinates geographical 00 ° 49' 00 "South latitude and 78 ° 48'30" West longitude. The experimental work lasted for three months. The treatments under study were as follows: T1 = organic fertilizer Agropesa (50L ha-1) Azotobacter spp.. (1 L ha-1)T2 = manure organic Agropesa (50L ha-1) Pseudomonas fluorescens (1L ha-1) T3 = manure organic Biol (50L ha-1) Azotobacter spp. (1 L ha-1)T4 = manure organic Biol (50L ha-1) Pseudomonas fluorescens (1L ha-1) xiii Was the design of completely randomized blocks DBCA with a total of four treatments and five replicates, with which was obtained 20 units experimentalesLos results were: the largest average in treatments at 30 days the organic fertilizer Agropesa Azotobacter spp. reaches He results were: plant height for the treatment of organic fertilizer Agropesa Azotobacter spp. used, became the highest elevation with 15.95, 31.90 and 43.75 cm 30, 45 and 60 days, in their respective order. Organic fertilizer treatment Agropesa Azotobacter spp. achievement its advantage in weight with 113.25 g; and yield per hectare with 1.13 t. without statistical difference among treatments in study.The study of regression and correlation between the variables was observed no significant relationship (P≤0. 05) and positive between height (X) and weight (and), found with a coefficient of correlation (= r) of 0,6889 and described by the equation: 63,736 1,1156 X, this indicates that higher, less is the weight. 1 Organic fertilizer treatment Agropesa Azotobacter spp., reported higher revenues with 63.12 USD. The most optimal utility came with treatment 1 compost Agropesa Azotobacter spp., with 8.70 USD. The best benefit/cost relationship was treatment 1 compost Agropesa Azotobacter spp., with 0.16.